Perancangan Sistem Informasi Desa berbasis Mobile dengan konsep Government To Citizen: Perancangan Sistem Informasi Desa berbasis Mobile dengan konsep Government To Citizen - Ahlis Noor Kholili; Muhammad Sulthony (INTECH, 2024)
In the current digital era, the advancement of information technology plays a pivotal role in improving the quality of life in rural communities. This research aims to develop a Mobile-Based Village Information System with a Government-To-Citizen concept, designed to provide easy and swift access to crucial information, including education, culinary, and automotive workshop details within the village environment. The application is equipped with features tailored to facilitate rural residents in accessing relevant information efficiently. The education information feature offers access to educational programs, scholarships, and training opportunities, contributing to the enhancement of literacy levels in the village. Meanwhile, the culinary information feature provides local culinary businesses with the chance to market their products, supporting the economic growth of village residents and ensuring sustainability for Micro, Small, and Medium Enterprises (MSMEs). Furthermore, the automotive workshop information feature streamlines the process of finding workshops or vehicle repair services, supporting the maintenance of residents' vehicles and contributing to the improvement of technical skills and business opportunities in the automotive sector. Research findings indicate that the implementation of this application has a positive impact on simplifying information access, subsequently contributing to the economic development of village residents and revitalizing the MSME sector. Thus, the Mobile-Based Village Information System with a G2C concept not only proves to be an effective solution for information retrieval but also serves as a catalyst for progress and well-being in rural communities in this digital age